DESIGN AND DEVELOPMENT OF DRUG STORAGE INFORMATION SYSTEM - Anugrah Putra Permana; Rosalina Rosalina (IT for Society, 2021)
Inventory is a stored material or item that will be used to fulfill certain purposes. Every company that carries out business activities generally has inventory. Inventories are goods that are stored for use or sale at a future date or period. Inventory system has an important role in every company, especially those engaged in purchasing good. In the health sector there is such a thing as a drug storage information system which function to monitoring drug stock supplies within a certain period of time. This system will monitoring every drug transaction In & Out or Buy & Sell. Benefits of this system are to keep drug stock, to have full control over inventory, and to analyse and make decision for future achievement.